A PSYCHOLOGY AND THREE PSYCHOLOGY PERSPECTIVES(STRUCTURALISM, HUMANISTIC PERSPECTIVE, PSYCHOANALYTIC PERSPECTIVE) - Sabani, Havva (International Scientific Journal Vision, 2017)
The aim of this study is to examine and explain what psycholo-gy is and how it is developed. All human knowledge is derived from human experience. Psychology has begun to develop since the second half of the 19th century. The German psychologist Wilhelm Wundt pioneered experimental psychology and Struc-turalism appeared as the first school of thought. After getting an idea what psychology in is important to soot a glance to the basic psychology approaches.